2019
DOI: 10.1016/j.dnarep.2019.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Role of Y-family translesion DNA polymerases in replication stress: Implications for new cancer therapeutic targets

Abstract: DNA replication stress, defined as the slowing or stalling of replication forks, is considered an emerging hallmark of cancer and a major contributor to genomic instability associated with tumorigenesis [1]. Recent advances have been made in attempting to target DNA repair factors involved in alleviating replication stress to potentiate genotoxic treatments. Various inhibitors of ATR and Chk1, the two major kinases involved in the intra-S-phase checkpoint, are currently in Phase I and II clinical trials [2]. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 73 publications
2
30
0
Order By: Relevance
“…POLη (green) and nuclei stained (blue) with DAPI. Preprints (www.preprints.org) | NOT PEER-REVIEWED | Posted: 30 September 2019 doi:10.20944/preprints201909.0338.v1Figure suggests that β-HPV E6 reduces POLη expression[40,63]. This is supported by our immunoblot analysis that shows β-HPV 8E6 causes a sizable decrease in POLη(Figure 6A).…”
supporting
confidence: 52%
See 1 more Smart Citation
“…POLη (green) and nuclei stained (blue) with DAPI. Preprints (www.preprints.org) | NOT PEER-REVIEWED | Posted: 30 September 2019 doi:10.20944/preprints201909.0338.v1Figure suggests that β-HPV E6 reduces POLη expression[40,63]. This is supported by our immunoblot analysis that shows β-HPV 8E6 causes a sizable decrease in POLη(Figure 6A).…”
supporting
confidence: 52%
“…Specifically, β-HPV E6 reduces the ATR-dependent phosphorylation required for XPA stabilization and NER function [37,38]. β-HPV E6 also attenuates stabilization of POLη, the TLS polymerase most relevant for bypassing UV lesions [39,40]. Further, while β-HPV E6 decreases CHK1 phosphorylation and total CHK1 abundance, signaling events further downstream were not attenuated [41].…”
Section: Introductionmentioning
confidence: 97%
“…In this pathway, errors in the newly synthesized strand are removed and the DNA is resynthesized by the replication machinery (112). Bulky abducts which remain unrepaired at DNA replication are bypassed by a process known as translesion synthesis (TLS), which allows restoration of the double stranded DNA prior to NER (113).…”
Section: Dna Repairmentioning
confidence: 99%
“…NER is responsible for physically removing UV-induced DNA lesions and it has been shown that an essential protein, XPA, is stabilized by ATR phosphorylation [37,38]. The TLS pathway helps bypass UV lesions primarily through the TLS polymerase, POLη, which is regulated by ATR and p53 [39,40]. Finally, ATM and ATR control cell cycle progression via phosphorylation of CHK1 and CHK2 [41][42][43].…”
Section: Introductionmentioning
confidence: 99%